Drought tolerant corn response to water availability - Newell, Trenton D. (Kansas State University, 2016)
Due to decreased availability of irrigation water in central and western Kansas and an increase in water restrictions, producers are looking for more efficient ways to use available irrigation water. Drought-tolerant technologies have become popular in hybrids for stress-prone environments across central and western Kansas and are marketed for their ability to produce greater grain yields with less water. The objective of this research was to understand how DT and non-DT corn hybrids respond in a wide range of environmental conditions in terms of soil water status change, canopy indicators of stress, dry matter partitioning, and grain yield. Soil water status change, yield, and canopy response characteristics of two DT hybrids, and one non-DT hybrid were compared at five locations over two years in rain-fed, semi-irrigated, or fully irrigated regimes making a total of 18 environments. Field experiments were established in 2014 and 2015 near Topeka, Scandia, Hutchinson, Garden City, and Tribune, KS. Two corn hybrids with different approaches drought tolerance (Pioneer 1151 AQUAmax, bred drought tolerance and Croplan 6000 DroughtGard, bred drought tolerance plus transgenic drought tolerance), and one hybrid with no specific drought tolerance characteristics but with proven performance in favorable environments (Croplan 6274) were used in the experiment. Soil moisture content (measured using a neutron moisture meter), canopy temperature, ear leaf temperature, and chlorophyll content were measured at tasseling (VT), milk or dough (R3-R4), and physiological maturity (R6) developmental stages. Grain yield was at all 18 environments, and biomass production was estimated at 14 of the environments. Hybrid plasticity of yield results show the response for Croplan 6000DG and Pioneer 1151AM differed, but Croplan 6274 was the same as both other hybrids at the 0.10 alpha level. Yields of all hybrids remained comparable in most environments, but as environment yields increased beyond 200 bu acˉ¹, Croplan 6000DG lagged behind Pioneer 1151AM. Hybrid harvest index plasticity shoed that all hybrids had the same response to environment in harvest index. Although, not statistically significant, when an environment supported favorable harvest index values greater than 0.40, it’s observed that Croplan 6000DG does have an improvement in harvest index relative to the Pioneer 1151AM and Croplan 6274.
Keywords: Corn; Drought tolerance; Deficit irrigation